Chronic pain: The prevalence of chronic pain in patients attending Soshanguve Community Health Centre - Funeka Faith Pandelani; Suzan Louisa Nnanile Nyalunga; Thanyani Pandelani (Taylor & Francis Group, 2024)
Introduction Chronic pain is a costly and incapacitating condition, with a projected global prevalence of 20%. In South Africa, almost one in five adults experience chronic pain. The aim of this study was to assess the prevalence of chronic pain and the association between chronic pain intensity and the interference of pain with life domains in patients attending a primary health care center.Methods We conducted a cross-sectional quantitative study on a sample of 331 patients at Soshanguve Community Health Centre. The data were collected using the Wisconsin Brief Pain Questionnaire, a validated scale for measuring pain.Results The mean age of participants was 51.6 years (SD = ±15.15, range = 18-86). The median age was 48 years (interquartile range = 40-64). The prevalence of chronic pain was 21.5% (95% confidence interval [CI] 17.0-25.9). Approximately 58% of participants were female, and female patients were affected more frequently than male patients. Chronic pain was observed to be 11.1% more prevalent in females than in males. Chronic pain mildly impacted general activity in 33.8% of patients (95% CI 23.9-45.4), mood in 42.3% (95% CI 31.4-53.8), walking ability in 29.6% (95% CI 20.2-41.0), relationships in 47.9% (95% CI 36.7-59.3), sleep in 31.0% (95% CI 21.4-42.5), enjoyment of life in 39.4% (95% CI 28.9-51.1), and normal working ability in 25.3% (95% CI 16.7-36.6).Conclusions Findings from this study show that among patients who attended the primary health care clinic, chronic pain was highly prevalent and interfered with their life domains. The intensity of pain was high in a significant proportion of patients. These findings provide invaluable information needed for the improvement of resources at the primary care level to comprehensively evaluate pain in our communities.